Examining of Social-Emotional and Moral Characteristics of a Child with Williams Syndrome and a Typically Developing Peer - Akgul-Cobanoglu, Fadime; Zorbay-Varol, Songul; Koksal, Mustafa Serdar (Ankara Univ, Fac Educational Sciences, 2025)
[No abstract available]
Keywords: Intellectual Disability; Mental-Retardation; Downs-Syndrome; Autism; Individuals; Adolescents; Anxiety; Adults; Performance; Population